Pengaruh Penambahan Pakan Cacing Sutera (Tubifex tubifex) Terhadap Pertumbuhan Ikan Jelawat (Leptobarbus hoevenii[Bleeker,1851]) - Ginting, Nesty Apulina Br; Ruyani, Aceng; Defianti, Aprina; Palindungan, Deni; Hidayat, Tomi (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: This study aims to determine the effect of growth of Jelawat fish given additional feed silkworm and pellets. Method: This study used Complete Randomized Design (RAL) with four treatments, five repeats. L. hoevenii were kept for 28 days with a countainer box with the same quality and quantity of water. Measurements are taken once every 2 weeks. Analysis of variance (ANOVA) was carried out on the measurement results, and continued with the Smallest Real Difference (BNT) test. Result: In treatment A with feed (100% pellets) resulted in weight growth (0.5 g), body length (3.4 mm), and body thickness (0.35 mm). In treatment B with feeding (Pellets 25% + T.tubifex 75%) resulted in weight growth (1.02 g), body length (24.6 mm), and body thickness (2.84 mm). In treatment C with feed (Pellets 50% +T.tubifex 50%) resulted in weight growth (0.54 g), body length (9.6 mm), and body thickness (1.71 mm). In treatment D with feeding (Pellets 75% + T.tubifex 25%) resulted in weight growth (0.34 g), body length (9.0 mm), and body thickness (1.37 mm). Conclusion: The addition of T. tubifex feed can have an influence on the growth of L. Hoevenii and the best treatment to produce good fish growth in this study is found in the B treatment given feed (Pellets 25% + T.Tubifex 75%) resulting in the highest growth with body weight growth (1.02 g), body length (24.6 mm), and body thickness (2.84) mm.